RELATIONSHIP OF ONLINE LEARNING WITH LEVELSTRESS ELEMENTARY SCHOOL CHILDREN FOR TIMECOVID-19 PANDEMIC IN ELEMENTARY SCHOOL - Wahyuni, Tini; Mien, Mien; Narmawan, Narmawan (PT. Nursing Genius Care, 2024)
Background: The sudden shift to online learning due to the Covid-19 pandemic significantly impacted the educational landscape, especially for elementary school children. This study focused on understanding how this transition influenced the stress levels experienced by students at SDN 78 Kendari.Purpose: to investigate the correlation between online learning and the stress levels experienced by elementary school children amidst the Covid-19 pandemic, specifically at SDN 78 Kendari. Methods: A correlation research design was employed, targeting students in grades 4-6, totaling a population of 204 individuals at SDN 78 Kendari. The study utilized a purposive sampling technique to select a sample size of 67 participants. Statistical analysis was carried out using the Spearman's rho test to establish the relationship between online learning and stress levels.Results: The findings revealed a significant relationship between online learning and stress levels at SDN 78 Kendari, denoted by a P-Value of 0.048. The statistical analysis demonstrated a negative coefficient number of -0.242. This negative correlation implies that increased engagement in online learning is associated with higher levels of stress among the students.Conclusion: The outcomes of this study indicate a noteworthy association between the frequency of online learning and elevated stress levels among elementary school children at SDN 78 Kendari. These findings emphasize the importance of considering the psychological impact of online education on young learners, urging the implementation of supportive measures to mitigate stress during remote learning situations.